2017
DOI: 10.1590/s0004-2803.201700000-23
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Distinguish Eosinophilic Esophagitis in Pediatric Patients

Abstract: -Background -Mast cells exert a substantial role in gastrointestinal allergic diseases. Therefore, it is reasonable to presume that mast cell may aid diagnosis in eosinophilic gastroenteropathy. Objective -To evaluate whether mast cell count in the esophageal epithelium can discriminate eosinophilic esophagitis, proton-pump inhibitor (PPI)-responsive eosinophilic esophagitis and gastroesophageal reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, clinical studies demonstrated elevated mast cell number in oesophagus biopsies from EoE patients . Moreover, mast cell accumulation in the oesophageal mucosa can be used in the diagnosis, in order to discern EoE from GERD …”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical studies demonstrated elevated mast cell number in oesophagus biopsies from EoE patients . Moreover, mast cell accumulation in the oesophageal mucosa can be used in the diagnosis, in order to discern EoE from GERD …”
Section: Discussionmentioning
confidence: 99%
“…Dellon et al [75] and others have found a dissociation between eosinophils and masts cells [76]. When eosinophil and mast cell counts are combined, there appears to be improved differentiation from gastroesophageal reflux disease (GERD) [75,77,78]. Other reports have noted increases in mast cells compared with GERD as well; however, no differences exist between PPIresponsive and nonresponsive EoE [77,78].…”
Section: Mast Cell Hyperplasia As a Biomarker In Eosinophilic Esophag...mentioning
confidence: 98%
“…When eosinophil and mast cell counts are combined, there appears to be improved differentiation from gastroesophageal reflux disease (GERD) [75,77,78]. Other reports have noted increases in mast cells compared with GERD as well; however, no differences exist between PPI-responsive and nonresponsive EoE [77,78]. When compared with eosinophils, the response of mast cell density to swallowed steroids and diet elimination has been shown to be variable [17 ▪▪ ,26,27 ▪▪ ,28,30,32].…”
Section: Mast Cell Hyperplasia As a Biomarker In Eosinophilic Esophag...mentioning
confidence: 99%
“…99 Another study reported that tryptase staining of mast cells has been found to differentiate EoE from reflux esophagitis. 100 In addition, the clinical symptom of dysphagia correlates best with esophageal gene transcripts predominantly involving mast cell-specific genes. 101 For other eosinophilic GI disorders, such as eosinophilic gastritis, eosinophilic enteritis, and eosinophilic colitis, the diagnostic criteria are less well defined.…”
Section: Gi Tractmentioning
confidence: 99%